2016
DOI: 10.1017/neu.2015.70
|View full text |Cite
|
Sign up to set email alerts
|

Association between AUTS2 haplotypes and alcohol dependence in a Japanese population

Abstract: This suggests that the rs6943555 and rs9886351 A-A haplotype might affect the vulnerability to alcohol dependence pathogenesis. Further studies are needed to confirm the reproducibility of the results of this study with increased numbers of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“… 11 17 Genotype and allele frequencies of this polymorphism in this study were not significantly different compared to that of our previous study (male: 23, female: 52, mean age: 35.36±9.06) (genotype: χ 2 (2)=0.271, p=0.873; allele: χ 2 (1)=0.557, p=0.455). 17 In addition, the A/A genotype (11.6%) and A allele frequencies (34.7%) in our subjects showed very little difference from those in Han Chinese subjects [Zhang et al: male: 192, female: 243, mean age: 37.6±10.8; Chen et al: male: 390 (genotyping in 373 males), mean age: 42.8±14.4; Dang et al: male: 355, female: 61, mean age: 37.13±5.23] (A/A genotype: 8.31–13.0%; A allele: 29.3–35.8%).10-12 On the other hand, in Polish Caucasian subjects (male: 1819, female: 2042, mean age: 45.72±14.91) the A/A genotype accounts for only 4.7% and the A allele 21%. 13 The genotype and allele frequencies of the polymorphism AUTS2 rs6943555 in Polish Caucasian subjects show significant differences from those in the Japanese population examined in this study [genotype: χ 2 (2)=39.4, p<0.01; allele: χ 2 (1)=40.1, p<0.01].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“… 11 17 Genotype and allele frequencies of this polymorphism in this study were not significantly different compared to that of our previous study (male: 23, female: 52, mean age: 35.36±9.06) (genotype: χ 2 (2)=0.271, p=0.873; allele: χ 2 (1)=0.557, p=0.455). 17 In addition, the A/A genotype (11.6%) and A allele frequencies (34.7%) in our subjects showed very little difference from those in Han Chinese subjects [Zhang et al: male: 192, female: 243, mean age: 37.6±10.8; Chen et al: male: 390 (genotyping in 373 males), mean age: 42.8±14.4; Dang et al: male: 355, female: 61, mean age: 37.13±5.23] (A/A genotype: 8.31–13.0%; A allele: 29.3–35.8%).10-12 On the other hand, in Polish Caucasian subjects (male: 1819, female: 2042, mean age: 45.72±14.91) the A/A genotype accounts for only 4.7% and the A allele 21%. 13 The genotype and allele frequencies of the polymorphism AUTS2 rs6943555 in Polish Caucasian subjects show significant differences from those in the Japanese population examined in this study [genotype: χ 2 (2)=39.4, p<0.01; allele: χ 2 (1)=40.1, p<0.01].…”
Section: Discussioncontrasting
confidence: 82%
“… 12 In addition, our previous study also reported that the haplotype consisting of the intronic polymorphisms rs6943555 and rs9886351 might affect the pathogenesis of alcohol dependence. 17 Thus, although an effect of the rs6943555-rs9886351 haplotypes on the development of personality traits was not observed in this study, it would be interesting for further analysis to be focused on AUTS2 haplotypes in future research.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We observed that several proteins identified in our GWAS for baseline ethanolamine concentration might display protein–protein interactions based on the STRING database. It should also be pointed out that several genes involved in the protein interactive network have been implicated in substance use disorders (Narita et al, 2016; Uhl et al, 2008; Yeung et al, 2017). For example, the autism susceptibility candidate 2 ( AUTS2 ) gene has implications for alcohol consumption (Narita et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They then found increased AUTS2 expression in the human prefrontal cortex from carriers of a minor AUTS2 allele, as well as altered expression between various high alcohol-preferring and low-alcohol-preferring mouse lines. The human importance of AUTS2 is further supported by another GWAS of alcohol consumption, a GWA meta-analysis of the maximum number of drinks consumed in 24 h, and a biased haplotype analysis [38,39,155]. Lastly, Schumann et al showed that reduced expression of the fly ortholog tay reduces EtOH sensitivity.…”
Section: Human Genome-wide Association Studies (Gwas)mentioning
confidence: 96%